Combined effect of flavonoid compounds and cytostatics in cancer treatment - Stompor, Monika; Podgórski, Rafał; Kubrak, Tomasz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Aim. The aim of the study was to review the literature on the combination of cytostatics with flavonoids as a promising way to improve the cancer therapy. Material and methods. A review of Polish and foreign literature was performed. The following databases were searched: PubMed, Scopus, Science Direct, and Polish Medical Bibliography. Literature analysis. Effective strategies to inhibit the progression of cancer are needed. Compounds of natural origin, including plant polyphenols, are a part of our diet. Due to their availability, and antioxidant properties, they may serve as efficacious adjuvants in cancer therapy, enhancing the effectiveness of chemotherapeutics. Epidemiological studies have shown an inverse relationship between diets rich in fruits, vegetables, and supplements, and the risk of all causes of death from cancer. Based on their diverse biological activity, flavonoids may be potential adjuvant therapeutic agents that act synergistically with cytostatics for treatment of many types of cancer. This review of the results is a summary the research on anticancer activity of flavonoids and may also raise consciousness of consumers, who will be able to compose their diet armed with the knowledge of preventive and therapeutic anticancer properties of food ingredients. There is need for further research on polyphenols of plant origin, including interactions among food components that coexist. Another important aspect is to understand how the activity of phytocompounds depends on concentration and the presence of additional factors (e.g. microflore, metal ions), which could possibly make a compound harmful, instead of having positive theraputics effect. Elucidation of the mechanisms involved in biological activity of the described phytocompounds is essential for a better understanding of their influence on an organism.
Keywords: flavonoids; anticancer drugs; co-delivery system; cytostatics